TINJAUAN TEOLOGIS PAEDAGOGIS KORELASI PENDIDIKAN AGAMA KRISTEN (PAK) GEREJA DAN KELUARGA DAN RELEVANSINYA BAGI PELAYANAN GEREJA MASA KINI - Trisno Kurniadi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2016)
There are things that are relevant but neglected, and there are also things that are closely related but are forgotten in family life and church service. That is the importance of Christian Religious Education in the context of family and church services today. But the correlation between Christian Religious Education and family would not be realized if there were no educators who understood the nature of Christian Religious education. Therefore through this paper, the author reviews theologically the pedagogical education of the Christian Religion (PAK) of the Church and family and their relevance to the service of the church today.